2018
DOI: 10.1111/btp.12598
|View full text |Cite
|
Sign up to set email alerts
|

Going to extremes for sodium acquisition: use of community land and high‐altitude areas by mountain gorillas Gorilla beringei in Rwanda

Abstract: Space use in mammals may be influenced not only by their primary foods, but also by localized sources of physiologically critical resources such as sodium‐rich plants. We examined how sodium acquisition influences habitat use in mountain gorillas (Gorilla beringei) in Rwanda which have increased the amount of time they forage on community land outside of Volcanoes National Park (VNP), where eucalyptus (Eucalyptus spp.) tree bark is their most frequently eaten food. We measured sodium content in samples from 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 80 publications
(143 reference statements)
1
11
0
Order By: Relevance
“…Thus, while high elevations can be harsh environments for primates, they can be an important part of a species home range when they provide a refugium for densely distributed, important food species. Similar behavior has been observed in mountain gorillas, who range at the altitudinal extreme of their range in Volcanoes National Park, Rwanda, to access sodium‐rich plant foods (Grueter, Wright et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…Thus, while high elevations can be harsh environments for primates, they can be an important part of a species home range when they provide a refugium for densely distributed, important food species. Similar behavior has been observed in mountain gorillas, who range at the altitudinal extreme of their range in Volcanoes National Park, Rwanda, to access sodium‐rich plant foods (Grueter, Wright et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…26,60]. Previous studies have demonstrated that several habituated gorilla groups in Bwindi range outside of the parks to feed on bananas-that may contain high sugar levels [61]-and eucalyptus trees that contain high sodium in both Bwindi and Virunga [61,62]. It is generally considered that such behaviors increased due to the habituation [60].…”
Section: Plos Onementioning
confidence: 99%
“…Bergstrom et al, 2019, Koops et al, 2019), and movement patterns (e.g. Grueter et al, 2018, McNaughton, 1988, Potts et al, 2015). In particular, it has been proposed that the availability of fallback food plays an important role in influencing the geographic and temporal distribution of many primate species (Grueter et al, 2009; Marshall et al, 2009), and the need to acquire specific nutrients can have important influence on their ranging and feeding behavior (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been proposed that the availability of fallback food plays an important role in influencing the geographic and temporal distribution of many primate species (Grueter et al, 2009; Marshall et al, 2009), and the need to acquire specific nutrients can have important influence on their ranging and feeding behavior (e.g. Bogart & Pruetz, 2011, Grueter et al, 2018, Hanson et al, 2003, Hohmann et al, 2019, Matsubayashi et al, 2011, Reynolds et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation